A qualitative exploration of Iranian smokers' experiences in terms of cigarette butt littering behaviour. Issue 2 (1st February 2022) - Dehdari, Tahereh
ABSTRACT: Although literature shows that Cigarette Butt (CB) is not just litter but a toxic waste which has harmful effects on the environment, a large number of smokers litter their CBs onto the ground. This study explored the experiences of smokers in terms of CB littering behaviour. A qualitative content analysis study was conducted in Tehran, Iran in 2019. Twenty-seven semi-structured in-depth interviews were done with smokers who discarded CB on the ground in outdoor public areas. Participants were asked about their experiences of littering CB. After the first interview, continuous data analysis began and continued up to saturation level. Three main categories including personal, social and structural factors emerged as the participants' experiences about discarding CB. These variables may suggest areas of focus for developing interventions to meet butt littering issue in Iran.